Keragaan Morfologi dan Fisiologi Seledri pada Pemberian Naungan dan Ekstrak Taoge - Trizayuni, Riskia; Warnita; Ardi; Zafitra; Via Permata Sari (Jurnal Agrosains dan Teknologi, 2025)
Celery offers a distinctive flavor to culinary dishes and has biopharmaceutical potential in addressing various health issues. Efforts to obtain high-quality celery in terms of appearance and content continue to be made to meet human needs. The objective of the study is to determine the morphological and physiological responses of celery plants to shade treatment and mung bean sprout extract. The experimental design used a completely randomized design with 2 factors, namely the provision of shade (without shade, 65% shade, 75% shade, and 85% shade) and the provision of bean sprout extract (without bean sprout extract, 10% bean sprout extract, and 30% bean sprout extract). Each treatment was repeated 3 times. Data were analyzed by analysis of variance and Duncan's New Multiple Range Test (5%). Results indicated that 85% shading combined with 30% mung bean sprout extract yielded the highest stomatal density. The same extract concentration also produced the highest chlorophyll a and total content. In contrast, 65% shading resulted in the largest leaf area of celery plants.